Hearing Impairments in Preterm Infants: Factors Associated with Discrepancies between Screening and Confirmatory Test Results - Jung Ho Han; Jeong Eun Shin; Soon Min Lee; Ho Seon Eun; Min Soo Park; Kook In Park (Korean Society of Neonatology, 2020)
Purpose The aim of the study was to investigate risk factors of hearing impairments in preterm infants and analyze factors associated with discrepancies between neonatal hearing screening (NHS) and confirmatory test results. Methods We analyzed the medical records of 352 preterm infants born at 23 to 32 weeks' gestational age (GA) who underwent both automated auditory brainstem response (aABR) and confirmatory ABR (cABR). Results Mean GA, mean birth weight, the incidence of small for GA and cesarean section birth were significantly different between the pass and refer groups on aABR and the normal and abnormal groups of cABR. On univariate analysis, bronchopulmonary dysplasia (odds ratio [OR], 2.74; 95% confidence interval [CI], 1.00 to 7.48), intraventricular hemorrhage (OR, 7.02; 95% CI, 1.59 to 31.05), and use of furosemide (OR, 3.84; 95% CI, 1.38 to 10.73) were the factors related to refer results on aABR. Periventricular leukomalacia (PVL; OR, 4.00; 95% CI, 1.39 to 11.52) and use of vancomycin (OR, 2.86; 95% CI, 1.22 to 6.73) were associated with abnormal cABR. Twenty-five (7.9%) infants had discrepant aABR and cABR results, particularly males and those in whom vancomycin was used. Conclusion PVL and use of vancomycin were confirmed as independent risk factors for hearing loss in infants born at less than 32 weeks' GA. Also, discrepancies between the screening and confirmatory test may occur, especially among male infants and those in whom vancomycin was used. The hearing of infants must be assessed more carefully in such groups regardless of NHS results.